Fracture characterization and prediction in a volcanic reservoir: A case study of the Permian Jiamuhe Formation in the Jinlong 2 Oil Field, Junggar Basin, China - He, Hui; Liu, Chang; Xie, Lin; Kong, Chuixian; He, Jianhong; li, Xianming; Ma, Pengshan (Journal of petroleum science and technology, 2024)
Fractures are the main flow channels for oil and gas in the Permian Jiamuhe Formation volcanic reservoir in the Jinlong 2 Oilfield at the northwestern margin of the Junggar Basin. According to core, thin section and image logging data analyses, the fractures in this area are dominantly semifilled or unfilled high-angle fractures, followed by semifilled low-angle oblique fractures, and vertical fractures. The image logging results show that the fractures are oriented nearly east–west, approximately parallel to the direction of the present-day maximum principal in situ stress, and they have good flow effectiveness. The volcanic reservoir fracture development is mainly affected by structure and lithology. The fractures are mostly distributed in strips along the faults. The closer to the fault, the greater the structural curvature and the more developed the fractures. The fractures of intermediate–acid volcanic lava and pyroclastic lava are well developed in the study area. Additionally, the fracture development characteristics of a single well are determined by calculating the fracture density, fracture dip angle, and fracture porosity. Combined with the prestack seismic prediction method, i.e., amplitude versus azimuth (AVAZ), the attenuation initial frequency attribute is selected to predict the fracture distribution characteristics of the Jiamuhe Formation volcanic reservoir.